(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Covid-19 pandemic changed the traditional working dimension of many sectors. Many sectors are still struggling and facing many difficulties to change their current working environment to adapt the Covid-19 pandemic. Education sector is foster in adapting this pandemic and change their teaching learning process from face-to-face methodology to remote learning. UNICEF reported that approximately 800 million learners got affected due to the spread of COVID-19. This outbreak makes a paradigm shift for many educationists from schools to colleges. The educationists are still fighting to survive this pandemic and introduce different approaches to enhance the teaching learning process. This paper presents a framework for auto assessing the programming courses using MOODLE learning management system with the support of four activities (quiz, debugging, fill the missing code and programming). The proposed framework was analysed with the help 176 students enrolled for Python Programming Courses. The grades acquired by all the students areanalysed and the result shows that student programming skill is drastically increases by using this auto assessment framework. The student perception on auto assessment framework was analysed based on the survey conducted with students. The survey responses clearly state that this kind of auto evaluation framework is helping the students to increasing their learning interest in any programming courses. Suggestion on adapting this kind of auto assessment framework in other programming courses is also presented